2019
DOI: 10.1108/intr-01-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Characters’ persuasion effects in advergaming

Abstract: Purpose The purpose of this paper is to explore advergaming to identify how users respond to characters in terms of forming brand trust and purchase intentions. The study shows that users will tend to trust brands when characters are congruent with product type and trust propensity. Design/methodology/approach In a 2×2×2 factorial design, the character presence/absence condition and product type (high vs low involvement) are between-subject, manipulated and dichotomous variables. Trust propensity is a measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…According to Table 1, the factors B1, B2 and B3 are related to the consumer’s propensity to distrust, which shows a general reluctance to be vulnerable to others and represents an individual’s belief that others are not benevolent and trustworthy (Chang & Fang, 2013). People with low‐trust propensity are doubtful of others’ behaviour facing unfamiliar situations and new people (Choi, 2019). Besides, the barrier B8, social risk, is the possibility that consumer’s acquaintances do not support online shopping behaviour (Wu et al., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Table 1, the factors B1, B2 and B3 are related to the consumer’s propensity to distrust, which shows a general reluctance to be vulnerable to others and represents an individual’s belief that others are not benevolent and trustworthy (Chang & Fang, 2013). People with low‐trust propensity are doubtful of others’ behaviour facing unfamiliar situations and new people (Choi, 2019). Besides, the barrier B8, social risk, is the possibility that consumer’s acquaintances do not support online shopping behaviour (Wu et al., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brand trust is a key component of cold BRQ (Nyffenegger et al ., 2015). Prior research shows that including realistic social cues in advergames enhances brand trust (Choi, 2019). Hence, it is anticipated that a realistic advergame experience will lead to BP intention via strongly impacting cold BRQ, and the trust component of cold BRQ will largely drive the BP intention.…”
Section: Hypothesis Formulationmentioning
confidence: 99%
“…Credibility, in this case, refers to the beliefs that celebrities convey to the public or their followers, such as; Expertise related to the knowledge and experience possessed by a supporter of a particular subject; and attractiveness is associated with the physical appearance, beauty, and sympathetic nature that exist in celebrity. When consumers believe that endorsers reflect their ideal self-concept and self-image, advertising evaluation can be positive, which can undoubtedly increase purchasing consumer products (Choi, 2019). In addition to these positive ratings, celebrity endorsements can also make these consumers more likely to show loyalty to a brand or product.…”
Section: Celebrity Endorsement On Purchase Intentionmentioning
confidence: 99%
“…The effect of celebrity support on product evaluation, showing it affects celebrities' fans, has also been studied (Agrawal & Kamakura, 1995). The researchers found that much of this effect resulted from consumer associations between stars and supported objects (Choi, 2019). Based on this explanation, the hypothesis is as follows:…”
Section: Celebrity Endorsement On Purchase Intentionmentioning
confidence: 99%